'Together … for only a moment': British newspaper constructions of altruistic non-commercial surrogate motherhood. (26th May 2016) - van den Akker, Olga; Camara, Isatou; Hunt, Ben
Abstract: Objectives: To explore how national altruistic surrogacy is framed in a representative selection of the British press.Methods: A study of 90 British national newspaper articles was carried out using the Lexis-Nexis database to search for articles on altruistic surrogacy. Content analysis of gain, loss, neutral frames and high or low alarm and vulnerability frames in the titles and the body of the text was carried out. The type of construction used in the article content was also analysed. Data were coded and consensus reached using a coding strategy specifically developed for the purposes of this study.Results: Titles and content were predominantly loss, high alarm and high vulnerability framed. The content was also gain framed, and written with a focus on the social and legal aspects differentially between the newspaper types.Discussion: The tabloid press emphasises social issues, and the middle market and serious press focus on legal issues of altruistic surrogacy. Selectively framed and reinforced information provided by the different newspapers reflect the different readership, with tabloid readers likely to be surrogates (mostly from lower socioeconomic strata) and serious/middle-market readers likely to be commissioning parents (mostly professionals).